Measuring the Impact of CSR Programs Using the Sustainability Compass:: A Case Study of the Sipandu Desi Program by PT PLN Nusantara Power UP Tanjung Awar - Awar - Gratha Ayunisa Agsyanti; Bilal Joko Suratno; Bayu Dwi Handoko; Felanza Herma Destia (Prospect: Jurnal Pemberdayaan Masyarakat, 2024)
The agricultural potential in Tuban Regency as a national food security hub is not exempt from issues that have caused its practices to diminish from generation to generation. PT PLN Nusantara Power, Tanjung Awar - Awar Generation Unit, located in Tuban Regency, contributes to the community through its CSR implementation. This paper presents the impact assessment of the SIPANDU DESI CSR Program (Integrated Agricultural Development System for Village Energy Synergy) by PT PLN Nusantara Power UP Tanjung Awar - Awar, using the concept of the Sustainability Compass. The method used in this research is descriptive qualitative with a case study approach to explain in detail how the program is implemented. This paper explains the program's implementation, which is based on agricultural issues and the company's needs, thereby creating Shared Value (CSV). The impact of the SIPANDU DESI program in addressing community needs is analyzed using the Sustainability Compass, including: (1) Nature, (2) Economy, (3) Society, and (4) Wellbeing.